Arctic Ocean Acidification Assessment: Summary for Policymakers - Arctic Monitoring and Assessment Programme (Arctic Monitoring and Assessment Programme, 2013)
Executive summary of the 2013 Arctic Ocean Acidification Assessment, including an update on the state of ocean acidification in the Arctic and how that acidification is impacting on the Arctic marine environment. It outlines each of the ten key findings in from the main report as well as the three recommendations to the Arctic Council.